A vogal /i/ en posición átona final de palabra no galelo medieval - Mariño Paz, Ramón (Revista de Filología Románica, 2009)
The aim of this article is to provide information about the vowel /i/ located in final atonic position in medieval Galician. After a complementary presentation about the velar vowels in the same position, the article contains a complete relation of the tonic vowels elevated by /i/ in the Galician dominion and an account of the extinction of this vowel in the Galician medieval written sources.
Keywords: Medieval Galician; Final atonic /i/; Language change